THE CRIMINAL LEGAL REGIME OF THE PREPARATORY ACTS - Popoviciu, Laura-Roxana (International Journal of Legal and Social Order, 2021)
This article deals with the particular aspects of the first phase of the external period of the intentional criminal activity, the phase of preparatory acts, essentially problematic, regarding the criminal legal regime and in particular their criminalization and sanctioning. In committing crimes, use of the preparatory acts had and has, not infrequently, a high frequency. Criminal law theorists have called "iter criminis" the criminal activity of a person, which, like any human activity has a development in time and space. During the course of the criminal activity, several phases can be distinguished. It is true that the legislator criminalizes and punishes acts that have produced a dangerous consequence, but it is no less negligible to take into account some stages that occur during the course of the crime and which, although they do not lead to dangerous consequences, are dangerous because they can they contribute either to the preparation of the commission of the crime, or they can present themselves even in the form of carrying out the criminal activity, which independently of the offender's will, or due to his intervention not to produce in the end the dangerous consequence. A form of committing the crime is represented by its preparation by externalizing acts, activities that ultimately contribute to the creation of favorable conditions for obtaining the dangerous consequence accepted by the offender. In this context, compared to the special implications that the preparatory acts have not infrequently had in the commission of criminal acts, the clarification of their problem represents both a doctrinal contribution and a practical necessity.